2000
DOI: 10.1111/j.1349-7006.2000.tb01022.x
|View full text |Cite
|
Sign up to set email alerts
|

TZT‐1027, an Antimicrotubule Agent, Attacks Tumor Vasculature and Induces Tumor Cell Death

Abstract: TZT-1027, a dolastatin 10 derivative, is an antimicrotubule agent with potent antitumor activity both in vitro and in vivo. In this study, we performed biochemical and histopathological examinations, and evaluated TZT-1027-induced tumoral vascular collapse and tumor cell death in an advanced tumor model, murine colon 26 adenocarcinoma. In addition, we studied the effects of TZT-1027 on cultured human umbilical vein endothelial cells (HUVEC). Tolerable doses of TZT-1027 induced tumor-selective hemorrhage within… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
46
0
2

Year Published

2003
2003
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(50 citation statements)
references
References 22 publications
2
46
0
2
Order By: Relevance
“…TZT-1027 is a novel antitumour agent that inhibits microtubule polymerisation and exhibits potent antitumour activity in preclinical models (Miyazaki et al, 1995;Kobayashi et al, 1997;Natsume et al, 2000Natsume et al, , 2003Natsume et al, , 2006Otani et al, 2000;Watanabe et al, 2000Watanabe et al, , 2006a. We investigated the effect of TZT-1027 on cell cycle progression with the use of tsFT210 cells, which can be synchronised in G 2 phase by incubation at 39.41C and consequent inactivation of Cdc2 (Osada et al, 1997;Tamura et al, 1999).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…TZT-1027 is a novel antitumour agent that inhibits microtubule polymerisation and exhibits potent antitumour activity in preclinical models (Miyazaki et al, 1995;Kobayashi et al, 1997;Natsume et al, 2000Natsume et al, , 2003Natsume et al, , 2006Otani et al, 2000;Watanabe et al, 2000Watanabe et al, , 2006a. We investigated the effect of TZT-1027 on cell cycle progression with the use of tsFT210 cells, which can be synchronised in G 2 phase by incubation at 39.41C and consequent inactivation of Cdc2 (Osada et al, 1997;Tamura et al, 1999).…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have recently shown that treatment with VTAs enhances the therapeutic effect of radiotherapy (Li et al, 1998;Rojiani, 2002, 2005;Horsman and Murata, 2003;Masunaga et al, 2004), consistent with the idea that the components of such combination therapy act in a complementary manner, with VTAs attacking the poorly oxygenated cell population in the central region of tumours and radiation killing the well-oxygenated proliferating cells at the tumour periphery (Li et al, 1998;Siemann and Rojiani, 2002;Wachsberger et al, 2003). TZT-1027 was previously shown to increase vascular permeability and to induce a decrease in tumour blood flow followed by a marked increase in tissue necrosis in the central region of tumour xenografts (Otani et al, 2000;Watanabe et al, 2006b). We have now shown that TZT-1027 treatment resulted in congestion and occlusion of tumour blood vessels followed by extensive necrosis of the tumour core, with only a thin rim of viable tumour cells remaining, in the H460 tumour model, suggesting that TZT-1027 acts as a VTA.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…7 Superior antivascular activity resulting in the collapse of the tumor vasculature was demonstrated, compared with the activities of taxanes and Vinca alkaloids. [8][9][10] The first clinical phase I study of TZT-1027 was initiated in 1994, and another four studies have since been completed; a phase II study is currently ongoing. [11][12][13] The major toxicity was hematological, in the form of neutropenia and leukopenia.…”
Section: Introductionmentioning
confidence: 99%
“…Vascular-targeting agents exploit the distinctive features of the tumor vasculature to irreversibly arrest blood flow in tumors (12). The resulting ischemia leads to a rapid cascade of secondary tumor cell death and the destruction of central areas of the tumor, which are normally most resistant to conventional therapies (13)(14)(15). ZD6126 is a novel vascular-targeting agent that is rapidly converted by serum phosphatases to ZD6126 phenol (N-acetylcolchinol), which disrupts the tubulin cytoskeleton of endothelial cells, resulting in conformational changes in immature, but not mature, endothe-lial cells (16).…”
Section: Introductionmentioning
confidence: 99%